ANALISIS WACANA HALLIDAY PADA PAMERAN TUNGGAL AHMAD JUNAID - Haryono, Haryono; Arfa, Muhammad; Gunalan, Sasih (Universitas Mercu Buana, 2024)
Fine art exhibitions are part of the discourse or publication that will be delivered by the owner of the work presented in public spaces. Where art exhibitions generally attempt to represent a value that is communicated through visual media in the form of paintings. Ahmad Jailani's exhibition is a fine arts event which is published in the form of an exhibition. Behind the exhibition, of course, there is another purpose that will be conveyed to the public. The aim of this research is to try to describe the dimensions of the artist's work in the form of paintings displayed and the dimensions of the curator presented in the form of a curatorial narrative. Because behind both visual and verbal tests there is a purpose and a relationship between one and another. This research uses a qualitative descriptive type of research where the research tries to draw relationships. The method of this research is the Halliday discourse analysis method which consists of what field of discourse is being discussed, the tenor of discourse who is involved in the conversation, and the mode of discourse (mode of discour) the language choices used by the media. The results of the research show that what is exhibited and what is opined is distorted, such as the work and the curatorial theme.